A pilot randomized controlled trial of online acceptance and commitment therapy versus compassion‐focused therapy for chronic illness. (5th August 2021) - Carvalho, Sérgio A.; Skvarc, David; Barbosa, Rosa; Tavares, Tito; Santos, Diana; Trindade, Inês A.
Abstract: Literature suggests that acceptance and commitment therapy (ACT) is effective in improving well‐being and in reducing psychopathological symptoms commonly experienced by people with chronic illness (CI). Compassion‐focused therapy (CFT) reduces psychological distress, especially in individuals with high levels of shame and self‐criticism, but few studies have explored CFT in CI. Additionally, studies almost exclusively compared ACT and CFT with inactive controls (wait‐list; treatment as usual). Also, there is an interest in developing cost‐effective mental health solutions, such as low‐intensity online psychological interventions. This randomized controlled trial (RCT) aimed to assess the acceptability and compare the efficacy of four‐session online ACT ( n  = 25) and CFT ( n  = 24) interventions in a sample of people with CI. Results showed both interventions were acceptable, with attrition rates at post‐intervention comparable to those found in similar studies (around 50%). Intention‐to‐treat analyses showed that participants presented significantly less illness‐related shame, less uncompassionate self‐responding and more valued living after the intervention, although no difference was found between conditions. Results were sustained at 3‐ and 6‐month follow‐up. Results did not find statistical differences between conditions through reliable change index (RCI). Correlation between demographics and RCI showed that, at post‐intervention, younger participants presented more behavioural awareness, men presented more valued action, and participants with CI for shorter periods presented less uncompassionate self‐responding and less anxiety. Results suggest that low‐intensity (four sessions) online ACT and CFT are cost‐effective approaches to promote mental health of individuals with CI. Results and limitations are thoroughly discussed.